Big revolution small country : the rise and fall of the Grenada revolution - Mandle, Jay R. (North-South Publishing Company LanhamUS, 1985)
Examines the political and economic situation which existed prior to the Grenada revolution. Assesses the role of the New Jewel Movement in the revolution attributing the lack of human resources as one of the reasons for its failure in implementing effectively, the socialist beliefs it expressed.